α‐Synuclein species in plasma neuron‐derived extracellular vesicles as biomarkers for iRBD - Xuemei Wang; Yuanchu Zheng; Huihui Cai; Wenyi Kou; Chen Yang; Siming Li; Bingxu Zhu; Jiayi Wu; Ning Zhang; Tao Feng; Xiaohong Li; Fulong Xiao; et al. (Annals of Clinical and Translational Neurology)
Abstract Objective Isolated REM sleep behavior disorder (iRBD) is considered as the strongest predictor of Parkinson's disease (PD). Reliable and accurate biomarkers for iRBD detection and the prediction of phenoconversion are in urgent need. This study aimed to investigate whether α‐Synuclein (α‐Syn) species in plasma neuron‐derived extracellular vesicles (NDEVs) could differentiate between iRBD patients and healthy controls (HCs). Methods Nanoscale flow cytometry was used to detect α‐Syn‐containing NDEVs in plasma. Results A total of 54 iRBD patients and 53 HCs were recruited. The concentrations of total α‐Syn, α‐Syn aggregates, and phosphorylated α‐Syn at Ser129 (pS129)‐containing NDEVs in plasma of iRBD individuals were significantly higher than those in HCs (p < 0.0001 for all). In distinguishing between iRBD and HCs, the area under the receiver operating characteristic (ROC) curve (AUC) for an integrative model incorporating the levels of α‐Syn, pS129, and α‐Syn aggregate‐containing NDEVs in plasma was 0.965. This model achieved a sensitivity of 94.3% and a specificity of 88.9%. In iRBD group, the concentrations of α‐Syn aggregate‐containing NDEVs exhibited a negative correlation with Sniffin’ Sticks olfactory scores (r = −0.351, p = 0.039). Smokers with iRBD exhibited lower levels of α‐Syn aggregates and pS129‐containing NDEVs in plasma compared to nonsmokers (pα‐Syn aggregates = 0.014; ppS129 = 0.003). Interpretation The current study demonstrated that the levels of total α‐Syn, α‐Syn aggregates, and pS129‐containing NDEVs in the plasma of individuals with iRBD were significantly higher compared to HCs. The levels of α‐Syn species‐containing NDEVs in plasma may serve as biomarkers for iRBD.